Functionalization of cellulose acetate fibers with engineered cutinases - Matamá, Maria Teresa (2010)
In the present work, we describe for the first time the specific role of cutinase on surface modification of cellulose acetate fibers. Cutinase exhibits acetyl esterase activity on diacetate and triacetate of 0.010 U and 0.007 U, respectively. An increase on the hydroxyl groups at the fiber surface of 25% for diacetate and 317% for triacetate, after a 24 h treatment, is estimated by an indirect assay. Aiming at further improvement of cutinase affinity toward cellulose acetate, chimeric cutinases are genetically engineered by fusing the 3′-end coding sequence with a bacterial or a fungal carbohydrate-binding module and varying the linker DNA sequence. A comparative analysis of these genetic constructions is presented showing that, the superficial regeneration of cellulose hydrophilicity and reactivity on highly substituted cellulose acetates is achieved by chimeric cutinases.